Pillars Of Pluralistic Education For Christian Education In The Context Of Multicultural Indonesia - I Made Suardana; I Putu Ayub Darmawan (Green Publisher Indonesia, 2022)
Indonesia is a nation with a plurality of people. This is an advantage that can produce strength as well as a problem if it is not interpreted properly. This article presents a literature study on the pillars of pluralism education for Christian education. According to the author there are three pillars of pluralism education for Christian education in the multicultural context of Indonesia, namely the pillar of the Authority that emphasizes education in bringing wealth of faith, the pillar of Identity, namely education as a realization of humanity, and the pillar of reality which emphasizes that education is the nature of freedom.